RISK ASSESSMENT IN SMALL AND MEDIUM – SIZED ENTERPRISES, SPECIFICS AND DIFFERENCES IN APPROACH - Komadinić, Velimir; Ilić, Dragomir (Journal of Applied Engineering Science, 2013)
The health and safety policy in Small and Medium-sized Enterprises (SMEs) demands a different approuch from that of big company. There are many differences between SMEs and their larger counterparts, and this must be taken into account when assessing risks in SMEs. The aim of this paper is analyzinghe characteristics of SMEs, current economic changes and their impact on developing the health and safety policy of the company and risk assessment.Also, we will describe the importance of labor inspection service,as an important external partners in supporting small and medium-sized enterprise with risk assessment.
Keywords: Labor inspection service; Risk Assessment; Characteristics; SMEs